First isolation of the Stephanoascus ciferrii in feline otitis in Brazil - Gomes,Angelita dos Reis (2014)
Ear infections in cats are uncommon, especially involving yeasts. This report describes the first isolation of the Stephanoascus ciferrii, teleomorph of the Candida genus, in a case of feline otitis in Brazil. The identification and characterization of Stephanoascus ciferrii were confirmed by the Vitek2 System (BioMerieux ®).